The Jarvik-2000 ventricular assist device implantation: how we do it - Zucchetta, Fabio; Tarzia, Vincenzo; Bottio, Tomaso; Gerosa, Gino (Annals of Cardiothoracic Surgery; Vol 3, No 5 (September 26, 2014): Mechanical Circulatory Support (I), 2014)
The Jarvik-2000 is a non-pulsatile axial-flow left ventricular assist device (LVAD) that is largely used in patients who present in end-stage heart failure, as a bridge to transplant support or destination therapy. From its first utilization, several implantation techniques have been elaborated, starting from a median sternotomy with cardiopulmonary bypass (CPB) support and moving towards a minimally invasive access with an off-pump strategy. Here we present the favored surgical technique used in our department to implant the Jarvik-2000, in a step-by-step fashion.